Design And Manufacture Of Information Systems For Monitoring The Implementation Of Single And Koppel Residential Building Construction Projects At Web-Based PT. Korang Aria Bima - Ridwan, M.; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2024)
PT. Korang Aria Bima is one of the many contractor companies located in the city of East Jakarta, established in 1983. The implementation of PT Korang Aria Bima's construction projects has not yet made computerized records of work plans and targets that must be achieved from each stage of project work, resulting in projects often experiencing setbacks that can harm the company. And to deal with these problems, a web-based construction project implementation monitoring application was created which aims to facilitate the company in monitoring the implementation of the project being worked on. This application is designed and built using PHP as a programming language and MySQL as a database. With this application, it is hoped that it can simplify existing processes.